3T MRI investigation of cardiac left ventricular structure and function in a UK population: The tayside screening for the prevention of cardiac events (TASCFORCE) study. Issue 5 (3rd May 2016) - Gandy, Stephen J.; Lambert, Matthew; Belch, Jill; Cavin, Ian; Crowe, Elena; Littleford, Roberta; MacFarlane, Jennifer A.; Matthew, Shona Z.; Martin, Patricia; Nicholas, R. Stephen; Struthers, Allan; Sullivan, Frank; et al.
Abstract : Purpose: To scan a volunteer population using 3.0T magnetic resonance imaging (MRI). MRI of the left ventricular (LV) structure and function in healthy volunteers has been reported extensively at 1.5T. Materials and Methods: A population of 1528 volunteers was scanned. A standardized approach was taken to acquire steady‐state free precession (SSFP) LV data in the short‐axis plane, and images were quantified using commercial software. Six observers undertook the segmentation analysis. Results: Mean values (±standard deviation, SD) were: ejection fraction (EF) = 69 ± 6%, end diastolic volume index (EDVI) = 71 ± 13 ml/m 2, end systolic volume index (ESVI) = 22 ± 7 ml/m 2, stroke volume index (SVI) = 49 ± 8 ml/m 2, and LV mass index (LVMI) = 55 ± 12 g/m 2 . The mean EF was slightly larger for females (69%) than for males (68%), but all other variables were smaller for females (EDVI 68v77 ml/m 2, ESVI 21v25 ml/m 2, SVI 46v52 ml/m 2, LVMI 49v64 g/m 2, all P < 0.05). The mean LV volume data mostly decreased with each age decade (EDVI males: –2.9 ± 1.3 ml/m 2, females: –3.1 ± 0.8 ml/m 2 ; ESVI males: –1.3 ± 0.7 ml/m 2, females: –1.7 ± 0.5 ml/m 2 ; SVI males: –1.7 ± 0.9 ml/m 2, females: –1.4 ± 0.6 ml/m 2 ; LVMI males: –1.6 ± 1.1 g/m 2, females: –0.2 ± 0.6 g/m 2 ) but the mean EF was virtually stable in males (0.6 ± 0.6%) and rose slightly in females (1.2 ± 0.5%) with age. Conclusion: LV reference ranges are provided in this population‐based MR study at 3.0T. The variables are similar to those described at 1.5T, including variations with age and gender. These data may help to support future population‐based MR research studies that involve the use of 3.0T MRI scanners. J. Magn. Reson. Imaging 2016;44:1186–1196.